Investigation of the Predictive Factors of Recurrent Ovarian Mucinous Cystadenoma - Ozcan, Aykut; Balikoglu, Meric; Alkan, Kaan Okan; Gulseren, Varol (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Rapid growth patterns and recurrence with variable rates have been reported in the literature, making mucinous cystadenomas different from other ovarian benign neoplasms. The study aimed to predict and prevent recurrence based on the obtained results. STUDY DESIGN: In this case-control study among the 2,341 patients who underwent surgery for ovarian cysts, 221 met the inclusion criteria. The 221 patients diagnosed with mucinous cystadenoma were categorized into two groups: 14 patients (6.3%) with recurrence and 207 patients (93.7%) without recurrence. Patients in these groups were compared in terms of demographic characteristics, ovarian cyst size, operative technique, type of surgery (oophorectomy or cystectomy), Ca19-9, CA125, and CEA values of the patients, and duration of postoperative follow-up. RESULTS: The mean age was statistically lower in the group with recurrence (27 ± 5 vs 44 ± 14; p<0.001). The follow-up period of recurrent cases was significantly longer (6.8 ± 3.5 vs 4.9 ± 2.2 years; p=0.045). The recurrence rate was significantly higher in patients who underwent cystectomy (p<0.001; odds ratio: 22.8). When all patients were examined, cystectomy was preferred in younger patients [31 (18-65) vs 48 (18-81); p<0.001]. According to regression analysis, cystectomy alone is an independent risk factor (p=0.041). CONCLUSION: Unlike conventional ovarian cystadenomas, mucinous cystadenomas should be followed up owing to the possibility of recurrence, especially when detected at an early age. Since cystectomy is the only independent risk factor, oophorectomy should be the primary treatment for patients >40 years of age who have no desire for childbearing.